Pendidikan Global dan Keberagaman Budaya: Menyongsong Pendidikan yang Lebih Terbuka dan Inklusif Berbasis AI - Everhard Markiano Solissa; Carolina Sasabone; Viona Sapulette; Heppy Sapulete (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article analyses the integration of global education, cultural diversity, inclusive education and artificial intelligence (AI) in building an open, adaptive and equitable learning ecosystem. The research employs a qualitative approach using a PRISMA-based Systematic Literature Review of 20 reputable scientific articles, which were analysed through thematic synthesis to identify patterns, conceptual contributions, and research gaps. The findings indicate that global education plays a role in fostering cross-cultural awareness and social responsibility, whilst cultural diversity demands learning designs that are responsive to differences in learners’ identities, languages, and experiences. Inclusive education serves as a key principle ensuring access, participation, and learning success for all learners without discrimination. On the other hand, AI contributes to personalised learning, learning analytics, and improved accessibility, yet it also poses challenges such as algorithmic bias, the digital divide, and privacy issues. The novelty of this research lies in a conceptual model that positions AI as an enabler within a humanistic, ethical, and culturally responsive educational framework, rather than as the central focus of learning. Consequently, the integration of these four aspects forms a crucial foundation for the development of a more inclusive, meaningful, and sustainable education system